Towards Zero Maternal Mortality: The Role of Policy Makers in Maternal Perinatal Audit Surveillance and Response - Ninik Dwi Ambarwati; Martha Irene Kartasurya; Cahya Tri Purnami (Poltekkes Kemenkes Palu, 2023)
The city of Semarang has formed a Maternal Perinatal Surveillance and Response audit committee team. The purpose of this study is to analyze the role of policy actors in the implementation of Maternal Perinatal Surveillance and Response Audit using the policy triangle framework of actors, content, context and process. This research was conducted qualitatively with a case study approach. The selection of informants was carried out purposively. Data collection by in-depth interviews with 6 main informants and 9 triangulation informants. Data were analyzed using thematic analysis, with the inclusion criteria of health workers having more than 3 years’ experience in handling maternal death cases. The results showed that the role of AMP-SR actors was optimal at the Health Service and Community Health Centers, the role of AMP-SR actors in hospitals was not optimal. Not all of the contents of the AMP-SR were understood by the midwives at the Health Centers and Hospitals, the identification and notifications were on time, the OVM and RMM reports were not complete, the maternal death assessment had not been all carried out, the responses had not been all followed up. The implementation process is hampered by limited staff and budget, medical devices are not routinely calibrated, the MPDN application has been used but is not optimal. In Conclusion, the role of policy makers is AMP-SR, intervening in reducing maternal mortality and improving the quality of care. Future research is expected to use the mixed method to find out the role of policymakers quantitatively and qualitatively.